Competitive strategies for water availability in two Mediterranean Quercus species - Nardini, A; Gullo, M A Lo; Salleo, S (Plant, Cell & Environment, 1999)
Competition for water availability was studied in a mixed natural stand of Quercus suber L. and Quercus cerris L. growing in Sicily by measuring diurnal changes of leaf conductance to water vapour (gL), water potential (ΨL) and relative water content (RWC) in April, July and October 1997 as well as the seasonal changes in root hydraulic conductance per unit leaf surface area (KRL). Quercus cerris behaved as a drought-tolerant species, with strong reductions of KRL, ΨL, and RWC in the summer. By contrast, Q. suber appeared to withstand summer drought by an avoidance strategy based on reducing gL, maintaining ΨL and RWC high and KRL at the same level as that measured in the spring. A ‘conductance ratio’ (CR) was calculated in terms of the ratio of gL to KRL. Seasonal changes of this ratio contrasted in the two species, thus suggesting that Q. suber and Q. cerris did not really compete for available water. In the summer, when Q. suber was extracting water from the soil to maintain high leaf hydration, Q. cerris had restricted water absorption, thus suffering drought but tolerating its effects. The possibility that cohabitation of drought-tolerant with drought-avoiding species can be generalized is also discussed.
Keywords: leaf conductance; leaf water status; Quercus cerris (Turkey Oak); Quercus suber (cork oak); root hydraulic conductance.

Seasonal changes of root hydraulic conductance (K RL) in four forest trees: an ecological interpretation - Nardini, A; Gullo, M A Lo; Salleo, S (Plant Ecology, 1998)
This paper deals with the possibility of relating root hydraulic parameters to an ecological index describing the continentality/oceanicity of four forest trees. Root hydraulic conductance (KR) of seedlings of Fagus sylvatica L., Quercus ilex L., Quercus suber L. and Quercus pubescens Willd. was measured in May, August and November 1996. KR was calculated in terms of the relation of the water ﬂow through intact root systems in situ measured with the pressure chamber, and the pressure driving the ﬂow. The sufﬁciency of the root system to supply the foliage was estimated by dividing KR by the seedlings leaf surface area (AL) thus obtaining KRL. In the spring, KRL was largest in F. sylvatica and smallest in Q. pubescens with intermediate values recorded in Q. ilex and Q. suber. All the species studied showed a large decline in KRL just prior to the winter rest except for Q. suber which mantained KRL approximately constant through the period of study. In most cases, KRL changed in accordance with analogous changes in the ﬂow. When the total seedlings’ leaf surface area (AL) was plotted versus KRL, it appeared that KRL of Q. pubescens increased with AL, proportionally, while KRL of F. sylvatica was inversely related to AL. This, together with the largest KRL recorded in the summer in Q. pubescens, was interpreted as advantageous to this species (which is adapted to semi-arid environments) in that: (a) roots could supply water to foliage efﬁciently even during the adverse season and (b) the foliage growth could be sustained even in summer. No statistically signiﬁcant relation of KRL to the continentality index calculated for the four species studied on the basis of their European distribution, was found to exist. Nonetheless, our data appear to be encouraging for future research aimed at better interpreting the typical distribution areas of plant species.
Keywords: continentality index; Fagus sylvatica; Quercus ilex; Quercus pubescens; Quercus suber; root hydraulic efficiency